The influence of flow velocity on coal fines output and coal permeability in the Fukang Block, southern Junggar Basin, China. Issue 1 (December 2017) - Tao, Shu; Tang, Dazhen; Xu, Hao; Li, Song
Abstract Coal samples were cut into cores to perform a flow velocity sensitivity (FVS) analysis under varying initial permeability, confining pressures, injection volumes, and injection intensities. The results show that the permeability and the output of the coal fines decrease with an increase in confining pressures at a constant displacement velocity. A critical flow velocity exists for the migration of relatively large coal fines. Below this critical flow velocity, very small coal fines can be transported out of the coal by the fluid, slightly increasing the coal permeability. However, larger coal fines are transported at a higher flow velocity, which may block the effective seepage paths and reduce coal permeability, inducing FVS. Moreover, as the flow velocity and the injection volume increase, the permeability damage rate increases, but the rate of increase in the permeability damage decreases. The damage to the permeability due to FVS mainly occurs in the early stage of coal fines migration, and an abrupt increase in the flow velocity can damage reservoirs and induce substantial coal fines generation. Thus, maintaining a stable effective strength and a controlled depressurization rate during drainage can effectively constrain coal fines output and decrease permeability damage within coal reservoirs.